Dynamic regulation of anthocyanin biosynthesis at different light intensities by the BT2-TCP46-MYB1 module in apple - Jian‐Ping An; Yajing Liu; Xiaowei Zhang; Si‐Qi Bi; Xiao‐Fei Wang; Chun‐Xiang You; Yu‐Jin Hao (2020)
Abstract Teosinte branched1/cycloidea/proliferating (TCP) transcription factors play a broad role in plant growth and development, but their involvement in the regulation of anthocyanin biosynthesis is currently unclear. In this study, anthocyanin biosynthesis induced by different light intensities in apple (Malus domestica) was found to be largely dependent on the functions of the MdMYB1 and MdTCP46 transcription factors. The expression of MdTCP46 was responsive to high light intensity, and under these conditions it promoted anthocyanin biosynthesis by direct interactions with MdMYB1 that enhanced the binding of the latter to its target genes. MdTCP46 also interacted with a bric-a-brac/tramtrack/broad (BTB) protein, MdBT2, that is responsive to high light intensity, which ubiquitinated MdTCP46 and mediated its degradation via the 26S proteasome pathway. Our results demonstrate that the dynamic regulatory module MdBT2-MdTCP46-MdMYB1 plays a key role in modulating anthocyanin biosynthesis at different light intensities in apple, and provides new insights into the post-transcriptional regulation of TCP proteins.